An analytical approach to evaluate the performance of graphene and carbon nanotubes for NH3 gas sensor applications - Akbari, Elnaz; Arora, Vijay Kumar; Enzevaee, Aria; Ahmadi, Mohamad. T.; Saeidmanesh, Mehdi; Khaledian, Mohsen; Karimi, Hediyeh; Yusof, Rubiyah (Beilstein Journal of Nanotechnology, 2014)
Carbon, in its variety of allotropes, especially graphene and carbon nanotubes (CNTs), holds great potential for applications in variety of sensors because of dangling π-bonds that can react with chemical elements. In spite of their excellent features, carbon nanotubes (CNTs) and graphene have not been fully exploited in the development of the nanoelectronic industry mainly because of poor understanding of the band structure of these allotropes. A mathematical model is proposed with a clear purpose to acquire an analytical understanding of the field-effect-transistor (FET) based gas detection mechanism. The conductance change in the CNT/graphene channel resulting from the chemical reaction between the gas and channel surface molecules is emphasized. NH3 has been used as the prototype gas to be detected by the nanosensor and the corresponding current–voltage (I–V) characteristics of the FET-based sensor are studied. A graphene-based gas sensor model is also developed. The results from graphene and CNT models are compared with the experimental data. A satisfactory agreement, within the uncertainties of the experiments, is obtained. Graphene-based gas sensor exhibits higher conductivity compared to that of CNT-based counterpart for similar ambient conditions.
Keywords: carbon nanotube (CNT); conductance; FET-based gas sensor; graphene

(untitled) - Xu, K.; Tian, X.; Wu, C.; Liu, J.; Li, M.; Sun, Y.; Wei, F. (Sci. China, Ser. E: Technol. Sci., 2013)

(untitled) - Rahmani, M.; Ahmadi, M. T.; Karimi, H. F. A.; Kiani, M. J.; Akbari, E.; Ismail, R. (Sens. Lett., 2013)

(untitled) - Kiani, M. J.; Ahmadi, M. T.; Akbari, E.; Karimi, H.; Che Harun, F. K. (Key Eng. Mater., 2013)

(untitled) - Amiri, I. S.; Ali, J. (Nanosci. Nanotechnol. Lett., 2013)

(untitled) - Amiri, I. S.; Ahsan, R.; Shahidinejad, A.; Ali, J.; Yupapin, P. P. (Commun., IET, 2012)

(untitled) - Amiri, I. S.; Rahim, F. J.; Arif, A. S.; Ghorbani, S.; Naraei, P.; Forsyth, D.; Ali, J. (Life Sci. J., 2013)

(untitled) - Yang, E. H. (Proc. SPIE, 2010)

(untitled) - Akbari, E.; Ahmadi, M. T.; Kiani, M. J.; Feizabadi, H. K.; Rahmani, M.; Khalid, M. (J. Comput. Theor. Nanosci., 2013)

(untitled) - Akbari, E.; Yusof, R.; Ahmadi, M. T.; Enzevaee, A.; Kiani, M. J.; Karimi, H.; Rahmani, M. (J. Nanomater., 2014)

(untitled) - Das, S.; Lahiri, I.; Kang, C.; Choi, W. (Proc. SPIE, 2011)

(untitled) - Kiga, N.; Takei, Y.; Inaba, A.; Takahshi, H.; Matsumoto, K.; Shimoyama, I. (CNT-FET gas sensor using a functionalized ionic liquid as gate, IEEE 25th International Conference on Micro Electro Mechanical Systems (MEMS), 2012, Paris, France, 29.1.2012-2.2.2012)

(untitled) - Arora, V. K.; Tan, M. L. P.; Gupta, C. (J. Appl. Phys., 2012)

(untitled) - Arora, V. K.; Bhattacharyya, A. (Nanoscale, 2013)

(untitled) - Chin, H. C.; Bhattacharyya, A.; Arora, V. K. (Carbon, 2014)

(untitled) - Iijima, S. (Nature, 1991)

(untitled) - Karamdel, J.; Amadi, M. T.; Majlis, B. Y.; Dee, C. F.; Ismail, R. (Formulation and Simulation for Electrical Properties of a (5,3) Single Wall Carbon Nanotube, IEEE International Conference on Semiconductor Electronics, 2008. ICSE 2008, Johor Bahru, Malaysia, 25.11.2008-27.11.2008, 2008)

(untitled) - Salvetat, J.-P.; Bonard, J.-M.; Thomson, N. H.; Kulik, A. J.; Forró, L.; Benoit, W.; Zuppiroli, L. (Appl. Phys. A: Mater. Sci. Process., 1999)

(untitled) - Mousavi, H. (Commun. Theor. Phys., 2011)

(untitled) - Yang, L.; Park, C.-H.; Son, Y.-W.; Cohen, M. L.; Louie, S. G. (Phys. Rev. Lett., 2007)

(untitled) - Son, Y.-W.; Cohen, M. L.; Louie, S. G. (Phys. Rev. Lett., 2006)

(untitled) - Amiri, I. S.; Afroozeh, A.; Bahadoran, M. (Chin. Phys. Lett., 2011)

(untitled) - Heller, I.; Janssens, A. M.; Männik, J.; Minot, E. D.; Lemay, S. G.; Dekker, C. (Nano Lett., 2008)

(untitled) - Sivasathya, S.; Thiruvadigal, D. J. (Asian J. Chem., 2013)

(untitled) - Uchida, K.; Saitoh, M.; Kobayashi, S. (Carrier transport and stress engineering in advanced nanoscale transistors from (100) and (110) transistors to carbon nanotube FETs and beyond, IEEE International Electron Devices Meeting, 2008. IEDM 2008, San Francisco, CA, USA, 15.12.2008-17.12.2008, 2008)

(untitled) - Ding, L.; Wang, S.; Zhang, Z.; Zeng, Q.; Wang, Z.; Pei, T.; Yang, L.; Liang, X.; Shen, J.; Chen, Q.; Cui, R.; Li, Y.; et al. (Nano Lett., 2009)

(untitled) - Zhang, J.; Zhang, R.; Wang, X.; Feng, W.; Hu, P.; O’Neill, W.; Wang, Z. (J. Micromech. Microeng., 2013)

(untitled) - Amiri, I. S.; Nikoukar, A.; Shahidinejad, A.; Anwar, T.; Ali, J. (Life Sci. J., 2013)

(untitled) - Wang, Y.; Huang, B.-C.; Zhang, M.; Woo, J. C. S. (Microelectron. Reliab., 2012)

(untitled) - Amiri, I. S.; Ali, J. (Quantum Matter, 2013)

(untitled) - Ding, W.; Hayashi, R.; Suehiro, J.; Zhou, G.; Imasaka, K.; Hara, M. (IEEE Trans. Dielectr. Electr. Insul., 2006)

(untitled) - Cho, T. S.; Lee, K.-J.; Kong, J.; Chandrakasan, A. P. (The design of a low power carbon nanotube chemical sensor system, 45th ACM/IEEE Design Automation Conference, 2008, Anaheim, CA, USA, 8.6.2008-13.6.2008, 2008)

(untitled) - Nguyen, L. Q.; Phan, P. Q.; Duong, H. N.; Nguyen, C. D.; Nguyen, L. H. (Sensors, 2013)

(untitled) - Arakelyan, V. M.; Aleksanyan, M. S.; Hovhannisyan, R. V.; Shahnazaryan, G. E.; Aroutiounian, V. M.; Hernadi, K.; Nemeth, Z.; Forro, L. (J. Contemp. Phys. (Arm. Acad. Sci.), 2013)

(untitled) - Xie, H.; Sheng, C.; Chen, X.; Wang, X.; Li, Z.; Zhou, J. (Sens. Actuators, B, 2012)

(untitled) - McEuen, P. L.; Fuhrer, M. S.; Park, H. (IEEE Trans. Nanotechnol., 2002)

(untitled) - Huang, B.; Li, Z.; Liu, Z.; Zhou, G.; Hao, S.; Wu, J.; Gu, B.-L.; Duan, W. (J. Phys. Chem. C, 2008)

(untitled) - Ahmadi, M. T.; Ismail, R.; Tan, M. L. P.; Arora, V. K. (J. Nanomater., 2008)

The Physics of Fullerene-Based and Fullerene-Related Materials - Dresselhaus, M. S.; Dresselhaus, G.; Eklund, P. C.; Rao, A. M. (Carbon nanotubes, 2000)

(untitled) - Ahmadi, M. T.; Johari, Z.; Amin, N. A.; Mousavi, S. M.; Ismail, R. (Carbon nanotube conductance model in parabolic band structure, IEEE International Conference on Semiconductor Electronics (ICSE), Melaka, Malaysia, 28.6.2010-30.6.2010, 2010)

(untitled) - Anantram, M. P.; Léonard, F. (Rep. Prog. Phys., 2006)

(untitled) - Ahmadi, M. T.; Johari, Z.; Amin, N. A.; Fallahpour, A. H.; Ismail, R. (J. Nanomater., 2010)

Electronic Transport in Mesoscopic Systems - Datta, S. (Cambridge University Press, 2002)

(untitled) - Peres, N. M. R.; Neto, A. H. C.; Guinea, F. (Phys. Rev. B, 2006)

Asymptotic expansions: their derivation and interpretation - Dingle, R. B. (Academic Press, 1973)

(untitled) - Zaharah, J.; Ahmadi, M. T.; Chek, D. C. Y.; Amin, N. A.; Ismail, R. (J. Nanomater., 2010)

(untitled) - Kažukauskas, V.; Kalendra, V.; Bumby, C. W.; Ludbrook, B. M.; Kaiser, A. B. (Phys. Status Solidi C, 2008)

(untitled) - Gunlycke, D.; Areshkin, D. A.; White, C. T. (Appl. Phys. Lett., 2007)

(untitled) - Yoon, H. J.; Jun, D. H.; Yang, J. H.; Zhou, Z.; Yang, S. S.; Cheng, M. M.-C. (Sens. Actuators, B, 2011)

(untitled) - Xia, J.; Chen, F.; Li, J.; Tao, N. (Nat. Nanotechnol., 2009)

(untitled) - Berger, C.; Song, Z.; Li, X.; Wu, X.; Brown, N.; Naud, C.; Mayou, D.; Li, T.; Hass, J.; Marchenkov, A. N.; Conrad, E. H.; First, P. N.; et al. (Science, 2006)

(untitled) - Brey, L.; Fertig, H. A. (Phys. Rev. B, 2006)

(untitled) - Peng, N.; Zhang, Q.; Chow, C. L.; Tan, O. K.; Marzari, N. (Nano Lett., 2009)